Religion-Based Social Relations in Police Practice in Managing Klitih in the Special Region of Yogyakarta - Wahyu Agha Ari; Prawitra Thalib (Jurnal Sosiologi Agama, 2025)
In recent years, the phenomenon of klitih in the Special Region of Yogyakarta (DIY) has caused widespread public concern. Although the police have the authority to enforce the law, addressing this crime is insufficient when relying solely on repressive measures. This article examines how police practices in DIY utilize religion-based social relations—namely forms of collaboration involving religious leaders, majelis taklim, pesantren, and Islamic educational institutions—to manage klitih-related crime. Using a qualitative approach through literature review, interviews, and observation, the study finds that the police have developed various collaborative programs such as religiously framed public safety outreach, mentoring for at-risk youth through majelis taklim, and preventive partnerships with pesantren and dakwah communities. This religion-based approach has proven effective in engaging the moral dimensions of youth, strengthening community social control, and fostering a sense of solidarity between law enforcement, community members, and religious leaders. Nevertheless, its implementation faces several challenges, including limited resources, resistance among some youths, and uneven program continuity. This article asserts that religion-based social relations contribute significantly to expanding the police’s role as inclusive, preventive, and contextually grounded guardians of public order within a religious society.